A Novel Heuristic Algorithm for Minimum Compliance Topology Optimization - BOCHENEK, Bogdan; MAZUR, Monika (Engineering Transactions, 2016)
The implementation of efficient and versatile methods to the generation of optimal topologies for engineering structural elements is one of the most important issues stimulating progress within the structural topology optimization area. Over the years, optimization problems have been typically solved by the use of classical gradient-based mathematical programming algorithms. Nowadays, these traditional techniques are more often replaced by other algorithms, usually by the ones based on heuristic rules. Heuristic optimization techniques are gaining widespread popularity among researchers because they are easy to implement numerically, do not require gradient information, and one can easily combine this type of algorithm with any finite element structural analysis code. In this paper, a novel heuristic algorithm for a minimum compliance topology optimization is proposed. Its effectiveness is illustrated by the results of numerical generation of optimal topologies for selected plane structures.